Expression Profiling of Genes Associated with the Pathogenesis of Recurrent Laryngeal Papillomatosis: Molecular pathogenesis of RLP - Muhammad Yasir Khan; Zahra Sarwar; Mavra Sarwar; Saif Ullah Khan; Muhammad Sarwar Khan; Rashida Khan; Qaisar Mansoor (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2024)
Recurrent Laryngeal Papillomatosis (RLP) affects the aero-digestive intersection with a predilection for the glottis. It is predominantly a juvenile-onset disease. The main infectious agents are type 6 and 11 low-risk human papillomaviruses. Understanding the genetic changes associated with the pathogenesis of RLP might prove helpful to mark the severity and aggression of the disease and lead to better clinical management. Clinically diagnosed RLP children below the age of 12 years along with a control sample of healthy tissue from age and gender-matched children undergoing tonsillectomy and thyroidectomy were collected. All the samples were processed for total RNA extraction followed by first strand cDNA synthesis. Real-time PCR was done to determine the relative gene expression of EGFR, ER-α, CXCL12, CXCR4, GLUT-1, IGF-1, HIF-1α, VEGF, ERK1/2, PI3K and AKT genes along with GAPDH as gene of reference. An increase in the transcriptional level expression of the genes CXCL12/CXCR4, GLUT-1, EGFR, ER-α, and IGF-I was observed in the cases in comparison to the controls. The expression of HIF-1α, VEGF, PI3K, and AKT genes was not noticeably elevated. The gene expression analysis may open the avenues for possible strategies that can be employed to treat RLP more effectively.